A Constant Rank Constraint Qualification in Continuous-Time Nonlinear Programming - do Monte, Moisés Rodrigues Cirilo (2020)
The paper addresses continuous-time nonlinear programming problems with equality and inequality constraints. First and second order necessary optimality conditions are obtained under a constant rank type constraint qualification. The first order necessary conditions are of Karush-Kuhn-Tucker type.